Pengembangan Sistem Forum pada Aplikasi Komunitas Bonsai Indonesia Berbasis Web - Rifki Fajar Ramadhani; Nurudin Santoso; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Bonsai is a plant that has many fans, ranging from young people to the elderly. Bonsai is a plant that is reduced in size and planted in a pot so that it can be decorated at will by the owner. With so many lovers of this plant scattered, the bonsai lovers community can also be said to be many and there are in almost every region and the authors take the example of the Indonesian Bonsai Lovers Association (PPBI) Batu. Because there is a community, there is also a forum that discusses bonsai plants organized by the related community. However, if the forum is held between regions, not all community members can participate. Although there are several platforms that can be used as an alternative in overcoming this problem, but one representative from the PPBI Batu community said that comfort in their use was still lacking. In this study, the authors designed an online forum system for the Indonesian bonsai community that focuses on the existing forum problems. In its development, the authors use the Rapid Application Development (RAD) development method which is implemented with the laravel framework. Laravel itself is a framework that uses the programming languages ​​PHP, HTML, CSS, and Javascript. After the implementation is complete, the system is tested to ensure there are no defects in this application. Tests conducted include white box testing, black box testing, and usability testing using the SUS method. Tests carried out produce results that state that the system functions are 100% valid and running well. In SUS testing, this system obtained a value of 77.5 which makes this system into the acceptable category.